Genetic Diversity and Population Structure of IRRDB 1981 and Wickham Rubber Germplasm Based on EST-SSR - Fetrina Oktavia; Kuswanhadi Kuswanhadi; Dini Dinarty; Widodo Widodo; Sudarsono Sudarsono (AGRIVITA, Journal of Agricultural Science, 2017)
The accession of the IRDB 1981 (PN’81) population is a newly introduced and an important rubber tree germplasm while the Wickham clone is a commercial variety one. The objectives of this study were to assess the genetic diversity and the population structure of PN’81 populations and the Wickham clones using 15 EST-SSR loci. Results of the analysis showed that the evaluated SSR primers yielded polymorphic markers. The gSSR 268 primer pairs yielded the most informative markers while HBE 280 primers generated the lowest ones. Results of the genetic diversity analysis supported that the PN’81 population belonged to a single large natural population of rubber trees while the Wickham clones belonged to a different group than that of PN’81. The population structure analysis of the rubber accessions was also in agreement with the results of the genetic diversity analysis. The experiment also indicated that PN’81 populations would be useful for future rubber breeding in Indonesia, especially as the sources of parent clones for rubber tree hybridization programs and rubber tree genetic resource conservation.